2010
DOI: 10.1038/jid.2009.270
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Anaplastic Large Cell Lymphoma and Peripheral T-Cell Lymphoma NOS Show Distinct Chromosomal Alterations and Differential Expression of Chemokine Receptors and Apoptosis Regulators

Abstract: Primary cutaneous anaplastic large cell lymphoma (C-ALCL) has an indolent clinical course and favorable prognosis. On the contrary, primary cutaneous peripheral T-cell lymphoma not otherwise specified (PTL-NOS) shows aggressive clinical behavior. To identify genomic events relevant in the pathogenesis of these cutaneous T-cell lymphomas (CTCLs), we carried out array-based comparative genomic hybridization (CGH) analysis. Simultaneously, gene expression profiling was conducted to gain insight into gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
(70 reference statements)
3
45
1
Order By: Relevance
“…The existence of patients with mucocutaneous disease suggests mucosal CD30-positive T-cell lymphoproliferations may be biologically similar to cutaneous cases, possibly reflecting molecular features contributing to epitheliotropism of the CD30-positive T cells. 33 Oral involvement in patients with cutaneous mycosis fungoides typically occurs late in the clinical course and is associated with poor prognosis. 26 Our patient with mycosis fungoides (case 8) died of unrelated causes 19 months after presentation with disease in the nasal cavity, at which time he had persistent cutaneous disease but no evidence of mucosal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of patients with mucocutaneous disease suggests mucosal CD30-positive T-cell lymphoproliferations may be biologically similar to cutaneous cases, possibly reflecting molecular features contributing to epitheliotropism of the CD30-positive T cells. 33 Oral involvement in patients with cutaneous mycosis fungoides typically occurs late in the clinical course and is associated with poor prognosis. 26 Our patient with mycosis fungoides (case 8) died of unrelated causes 19 months after presentation with disease in the nasal cavity, at which time he had persistent cutaneous disease but no evidence of mucosal disease.…”
Section: Discussionmentioning
confidence: 99%
“…11,[37][38][39] Indeed, data from our group 22,27 and from others [23][24][25][26]28,29,[40][41][42][43] showed the presence of more complex chromosome aberrations in aggressive CTCL than in C-ALCL. 28,44 When telomeres become critically short, it is believed that their protective function is compromised and that cells follow the flow diagram process (Figure 7) with replicative senescence, crisis, escape from crisis, and maintenance of TL. 45 Our data support this theoretical process and also suggest that aggressive CTCLs are passed-over crisis cells.…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, genomic abnormalities were investigated in SS patient cells and cell lines, taking into consideration chromosome aberrations previously reported in SS patients by our group 27 and others. [23][24][25][26]28,29 For cases 2 and 17, AU (data not shown), c-MYC and centromere 8 fluorescent probes were chosen to investigate SS nuclei chromosomal status in combination with antibodies to delineate SS cells ( Figure 2E-H) or with peptide nucleic acid telomeric probes to evaluate TL ( Figure 2I-J). Image analysis revealed that abnormal chromosome content was restricted to both neoplastic SS T cells ( Figure 2E-H) and to nuclei with short telomeres, whereas cells with normal chromosome content showed long telomeres ( Figure 2I-J).…”
Section: Short Tl: a Hallmark Of Neoplastic Ss Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormalities of ALKÀALCL do not fully overlap with whose reported for other T-cell neoplasms, but can be shared with primary cutaneous ALCL. (11,45,57,58) The last observation is intriguing, indicating a high similarity between these two types, despite their diverse clinical features and outcomes, with a much better prognosis observed for primary cutaneous ALCL. (59) Two translocations have been recently reported in ALKÀALCL.…”
Section: Nodal Lymphomasmentioning
confidence: 99%